PERBANDINGAN KINERJA KEUANGAN PUSKESMAS RAWAT INAP YANG SUDAH DAN BELUM MENERAPKAN ISO 9001:2008 DI KABUPATEN TEMANGGUNG: Studi Kasus Pada Puskemas Ngadirejo dan Puskesmas Bejen - , FUAD FATKHURROHMAN, DR. Julita Hendrartini, drg, M.Kes, AAK. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Community Health Centerâs financial management must be based on Government Regulation No 71 of 2010 taking the form of a financial report. Community Health Center must also fulfill an international standard (ISO) 9001: 2008 to guarantee a sound improvement in the quality of health service. Community Health Centerâs annual evaluation results in Temanggung District of 2011 and 2012 have indicated that the Centerâs finance has produced different productivity in service and financial performance. This study is conducted to compare Inpatient Community Health Centers with ISO 9001:2008 and without ISO in Temanggung District. Method: This research is a comparative study with a case study plan. The sampling method is based on purposive sampling with the Community Health Centersâ analysis units. Data is obtained from the Centersâ administration data and from in-depth interviews with the Centersâ financial managers. Results: Financial performance in both Community Health Centers has shown stable relationship between the Centersâ efficiency and effectiveness in financial performance. Legal issues remain a major constraint in the Centersâ financial management. Factors influencing the Centersâ financial performance are not only financial management, but also unsatisfactory results in acquiring good governance. Conclusion: (1) indicate better financial performance in terms of long time compared to Non ISO Community Health Centers. Financial performance at ISO Community Health Centers in their initial certification is lower performance because it has been adaptation process ISO system and higher expenditure of capital cost for continous performance. (2) ISO Community Health Centersâ financial performance has been more effective and efficient compared to Non ISO Centers. ISO Centers will be, in the long run, more effective and efficient with cost saving in health service and better health quality compared with Non ISO Centers. (3) Community Health Centersâ financial management would be more dependable with the application of bottom-up system, and the report must be in accordance with Regulation No 8 of 2006 so that the Centersâ financial data can be interpreted well in order to improve the Centersâ performance. (4) The quality of the human resources, bureaucracy process as well as supporting means may prove to be obstacles in financial management of the Community Health Centers. Key words: financial performance, Community Health Centers, ISO 9001:2008